1997
DOI: 10.1523/jneurosci.17-08-02703.1997
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Long-Lasting Form of Odor Adaptation that Depends on the Carbon Monoxide/cGMP SecondMessenger System

Abstract: The diffusible messenger carbon monoxide (CO) has been proposed to mediate endogenous cyclic guanosine 3Ј,5Ј-monophosphate (cGMP) formation and sensory adaptation in vertebrate olfactory receptor neurons (ORNs). We have identified and characterized a long-lasting form of odor response adaptation (LLA) that operates at the level of isolated salamander ORNs and does not require any interactions from other cells. Manifestations of LLA are seen in reduced amplitude and prolonged kinetics of the cAMP-mediated excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 68 publications
4
54
0
1
Order By: Relevance
“…6) fits well with results from previous work indicating that cGMP-dependent Ca 2ϩ entry plays a significant role in a longlasting form of odor adaptation (Zufall and Leinders-Zufall, 1997). The main difference between cAMP and cGMP-dependent Ca 2ϩ entry seems to be in the time course of the signals.…”
Section: Implications For Transduction and Adaptation Mechanismssupporting
confidence: 90%
See 3 more Smart Citations
“…6) fits well with results from previous work indicating that cGMP-dependent Ca 2ϩ entry plays a significant role in a longlasting form of odor adaptation (Zufall and Leinders-Zufall, 1997). The main difference between cAMP and cGMP-dependent Ca 2ϩ entry seems to be in the time course of the signals.…”
Section: Implications For Transduction and Adaptation Mechanismssupporting
confidence: 90%
“…Removal of extracellular Ca 2ϩ results in a less transient cAMP-induced whole-cell current and eliminates the phasic-tonic behavior of odor currents during maintained stimulation (Kurahashi, 1990;Kurahashi and Shibuya, 1990;Zufall et al, 1991b;Kurahashi and Menini, 1997). Ca 2ϩ -dependent feedback regulation also can be initiated by the CO/ cGMP signaling system (Verma et al, 1993;Ingi and Ronnett, 1995;Leinders-Zufall et al, 1995a), which leads, via persistent activation of CNG channels by cGMP, to the induction of a long-lasting form of odor adaptation Zufall and Leinders-Zufall, 1997). Collectively, these results reveal complex effects of [Ca 2ϩ ] i in ORNs.…”
Section: Abstract: Olfactory Receptor Neurons; Cilia; Confocal Micromentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms underlying learning and memory may also be affected by CO: it could act as a retrograde messenger which links post and presynaptic sites (Wu & Wang, 2005). In salamander olfactory receptor neurons it has been shown that CO regulates long-term adaptation to odorant stimulation via its effect on cGMP levels (Zufall & Leinders-Zufall, 1997). Regarding studies on signal substances involved in pain, CO has been demonstrated to be involved in the regulation of neuropathic pain in mice (Li & Clark, 2003).…”
Section: Nervous Systemmentioning
confidence: 99%